Redesigning Life: Organic Chemistry and the Evolving Protein - Steven A. Benner (CHIMIA)
Techniques from synthetic chemistry, enzymology, and molecular biology are now making it possible to prepare sizeable amounts of proteins whose amino acid sequences have been systematically altered. These techniques permit chemists to apply structural theory to the behavior of biologically important macromolecules using the experimental methods formerly reserved for rather small molecules. This means that there are new experimental tests of hypotheses that connect the structure of proteins to their chemical behavior, their physiological function, and their evolution.